Are You Ready for a Crisis? Communication and Continuity in the Aftermath - Diana L Ashe; Rick Olsen; Colleen A Reilly; Matthew TenHuisen (Academic Chairpersons Conference Proceedings, 2020)
Institutions of higher education face numerous crises from natural disasters to mass shootings to sexual abuse scandals. Our interactive workshop will engage participants in planning, negotiating, and recovering from a variety of institutional crises. Participants will develop concrete plans for crisis preparation and recovery, including retrospective sensemaking.
Keywords: Crisis management; crisis communication; navigating ambiguity; retrospective sensemaking; strategic planning